(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
There is still a significant difference between Altajic agglutination. The words "sh" and "tch" are used in the East-West dialect. With the advent of the Karakalpak national tongue, the literary language’s attraction has changed. The majority of people speak in literary language’s endearing form on a regular basis. The Speaking language, the main variant of the Karakalpak language, is made up of two dialects.